1991
DOI: 10.3109/00365529108996243
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Endoscopic Hiatus Hernia and Gastroesophageal Reflux Symptoms

Abstract: Little is known about the relationship between hiatus hernia (HH) and gastroesophageal reflux symptoms (GERS). Nine hundred and thirty patients submitted to gastroscopy because of symptoms completed a self-administered questionnaire. Fourteen per cent showed esophagitis (ES) and 17% HH. Forty-nine per cent of the patients with HH had endoscopic ES, and 60% of those with ES had HH. The severity of ES was dependent (p less than 0.05) on both the presence and the size of HH. After exclusion of patients with pepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 19 publications
3
42
1
Order By: Relevance
“…First, although the FSSG score was highly correlated with endoscopic findings for GERD [27], the questionnaire results were based on selfreported symptoms rather than objective findings and that this was a limitation of the study, and second, the sample size of this study was relatively small compared to previous epidemiologic studies for GERD [20,41,42], and generalization of our findings to other populations may be premature. However, we would like to emphasize that this is the first study to focus on the influence of thoracic and lumbar spinal kyphosis and vertebral fractures on GERD among patients with osteoporosis.…”
Section: Discussionmentioning
confidence: 49%
“…First, although the FSSG score was highly correlated with endoscopic findings for GERD [27], the questionnaire results were based on selfreported symptoms rather than objective findings and that this was a limitation of the study, and second, the sample size of this study was relatively small compared to previous epidemiologic studies for GERD [20,41,42], and generalization of our findings to other populations may be premature. However, we would like to emphasize that this is the first study to focus on the influence of thoracic and lumbar spinal kyphosis and vertebral fractures on GERD among patients with osteoporosis.…”
Section: Discussionmentioning
confidence: 49%
“…Recently the first CDH survivor with esophageal adenocarcinoma has been described, 22 years after CDH repair [101]. Vanamo et al found that hiatus hernia was present in 30 patients, although as such this is not an uncommon finding in the adult population in the western world [102]. The overall prevalence of esophagitis was 54%, which is significantly higher than the expected 2% of endoscopically assessed esophagitis in the general adult population [103,104].…”
Section: Incidence Of Gerd In the Long Termmentioning
confidence: 96%
“…Makuuchi 10 reported that the complication of reflux esophagitis was recognized in 31.3% of patients suffering from hiatal hernia. Petersen et al, 11 after recognizing the presence of hiatal hernia in 60% of patients with reflux esophagitis, proposed that the two conditions are closely related. Both Patti et al 12 and Jones et al 13 stated that the severity of hiatal hernia and reductions in LES pressure constituted the most important factors when considering reflux esophagitis.…”
Section: Figmentioning
confidence: 98%